Struktur Cerkak Ing Kene Ana Cahya - Ratu, Aurora Kusuma; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
Javanese short stories are one of the genres in modern Javanese literature. Short storiesÂ (short stories) in modern Javanese literature are called cekak stories (cerkak). The focus ofÂ the study of Javanese short stories is short stories contained in Javanese magazines, such asÂ Jaya Baya magazine and Panyebar Semangat magazine. One of the stories that has panaÂ magazine panjebar semangat is a cerkak entitled "â€œIng Kene Ana Cahyaâ€ " by Sri Setya Rahayu. This research uses an objective approach and uses the theory of Structuralism. Based on the analysis of Structuralism in â€œIng Kene Ana Cahyaâ€ ing, it can be concluded that the cerkak uses a mixed flow. In the character element, there are several figures, namely Widuri, Suryadi and Pak Tamin. The background element is divided into two, namely the setting of the place and the background of time, the setting where the event occurs is on the House and Street, the background time on the story of â€œIng Kene Ana Cahyaâ€ occurs during the day. The point of view used in the story here is the third person point of view, where the author tells about the main character who experiences the events that occur.